Menyingkap Eksistensi Jati Diri Bangsa Melayu melalui Puisi Raja Ali Haji - Siti Marina Kamil; Hamidah Abdul Wahab (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2009)
National identity may be defined as a nation’s culture and language heritage reflected in the nation’s character, way of thinking or mentality. Raja Ali Haji  (1809-1870) was an important intellectual figure in the history of Malay literature and culture. His works, which include various texts covering history, language and statesmanship, have placed him as a pioneer ot Malay intellectuals his paper aims to analyse the element of national identity in his poetries, which was meant to be some kind of guidance for character building The book Puisi-puisi Raja Ali Haji (The Poems of Raja Ali Haji) serves as the man source for the analysis and a library research was conducted to do it. This paper prioritise on the Raja Ali Haji's character so that his thoughts can be comprehended and valued by various generations of the Malay society as well as by the global society.